2020
DOI: 10.3390/met10060756
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behaviour of High Strength Tool Steel 90MnCrV8 in Contact with Si3N4

Abstract: Tool steels are used in technological processes of forming and cutting and as cutting tools due to their good mechanical properties. During their working cycle, steels are exposed to several aggressive conditions, such as thermal stress, fatigue and various forms of wear. In this article, the selected 90MnCrV8 tool steel slid against the Si3N4 testing ceramic bearing ball. All measurements were performed on a universal tribometric device UMT TriboLab (TA Instruments, New Castle, Delaware, USA) under dry condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…It is worth noting that these cracks mainly propagate along the binder phases and eventually form fatigue spalling. Additionally, these spallings are ground between the tribo-pairs and become hard abrasive particles, resulting in a large number of ploughing on the surface of the WC ball [32]. However, when the crack encounters hard phases, such as WC, Cr 3 C 2 , or W 2 C, its propagation is effectively stopped, and delamination appears (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that these cracks mainly propagate along the binder phases and eventually form fatigue spalling. Additionally, these spallings are ground between the tribo-pairs and become hard abrasive particles, resulting in a large number of ploughing on the surface of the WC ball [32]. However, when the crack encounters hard phases, such as WC, Cr 3 C 2 , or W 2 C, its propagation is effectively stopped, and delamination appears (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“…What is more, like in the case of steel K340, these steels also, simultaneously, undergo adhesive wear, which is particularly visible for 90MnCrV8 (Figure 7c). Krbata et al [47] have demonstrated that the adhesive wear mechanism of this steel grade is more intensive at higher velocities during tribotesting. In turn, steel X155CrVMo12-1 exhibits the microcracking of carbides, which was probably caused by surface deformation of the material (Figure 7d).…”
Section: Wear Behaviourmentioning
confidence: 93%
“…Hardness was measured using the Vickers method on an Instron Wolpert 930 (Norwood, MA, USA) under a load of 49.05 N [ 14 ]. The results were averaged over five values for each sample.…”
Section: Methodsmentioning
confidence: 99%